Vital marking of articular chondrocytes by retroviral infection using green fluorescence protein - Hirschmann, F.; Verhoeyen, E.; Wirth, D.; Bauwens, S.; Hauser, H.; Rudert, M. (Osteoarthritis and cartilage, 2002)
Objective One of the main open questions in chondrocyte transplantation is the fate of the implanted cells in vivo. We intended to establish prerequisites for such studies in animal models and to show the feasibility of this approach in rabbits. Isolated articular chondrocytes were retrovirally marked using green fluorescence protein (GFP) as a cell-specific marker in order to allow an in vivo follow-up of these cells. Methods Chondrocytes from rabbits, sheep, cattle and humans were isolated and infected with murine leukemia virus-derived retroviruses carrying the GFP gene. The influence of the host range of three packaging cell lines (PA317, PT67, PG13), start cell concentrations, number of cell passages and number of infection cycles on the efficiency of infection was investigated. Stability of GFP expression was followed by FACS analysis, confocal imaging and fluorescence microscopy. For in vivo follow-up of GFP expression we used marked allogeneic chondrocyte populations grown on scaffold material and implanted them into full-thickness defects in knee joints of rabbits. ResultsRetroviruses from all three packaging cell lines were able to infect rabbit and human chondrocytes, whereas only retroviruses released from PG13 cells were able to infect sheep and bovine chondrocytes efficiently. Optimization of the infection with these viruses resulted in efficiencies of 60–90% GFP-expressing chondrocytes. Populations of 100% marked chondrocytes were obtained by cell sorting. GFP expression stability of such marked chondrocyte populations was followed in monolayer culture and in 3-D culture on different scaffold materials. The expression of GFP was stable on all tested materials for at least 4 weeks. In monolayer culture GFP expression was stable for more than 8 months. In vivo, we observed stable GFP expression in the transplants during a four-week time course. Conclusion Retroviral GFP gene transfer led to long-term expression in chondrocytes from rabbits, sheep, cattle and humans. Transgene expression and the number of implanted chondrocytes remain stable for at least 4 weeks in vivo. This method permits a rapid monitoring of chondrocytes and provides a basis for following the fate of these cells in vivo.